FORMATION OF NANOSTRUCTURES IN SEMICONDUCTORS AND THEIR THIN FILMS - Eshboltayev Iqbol Mamirjonovich; G‘ofurov Saidkamol Zokirjon ogli; Eshboltayev Ikromjon Iqbol ogli (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This paper presents a scientific analysis of the mechanisms of nanostructure formation in semiconductor materials and their thin films. The physicochemical factors influencing the formation of nano-scale structures, epitaxial growth processes, surface energy, and diffusion phenomena are discussed. In addition, the significance of nanostructured thin films in modern electronics and photonics is demonstrated.